Efficacy of THN201, a Combination of Donepezil and Mefloquine, to Reverse Neurocognitive Deficits in Alzheimer’s Disease - Droguerre, Marine; Duchêne, Adeline; Picoli, Christèle; Portal, Benjamin; Lejards, Camille; Guiard, Bruno P.; Meunier, Johann; Villard, Vanessa; Déglon, Nicole; Hamon, Michel; Mouthon, Franck; Charvériat, Mathieu (Frontiers in Neuroscience, 2020)
Donepezil (DPZ) is an acetylcholinesterase inhibitor used in Alzheimer’s disease to restore cognitive functions but is endowed with limited efficacy. Recent studies pointed out the implication of astroglial networks in cognitive processes, notably via astrocyte connexins (Cxs), proteins involved in gap junction intercellular communications. Hence, we investigated the impact on cognition of pharmacological or genetic modulations of those astrocyte Cxs during DPZ challenge in two rodent models of Alzheimer’s disease–like memory deficits. We demonstrated that the Cx modulator mefloquine (MEF) significantly enhanced the procognitive effect of DPZ in both models. In parallel, we determined that MEF potentiated DPZ-induced release of acetylcholine in hippocampus. Finally, local genetic silencing of astrocyte Cxs in the hippocampus was also found to enhance the procognitive effect of DPZ, pointing out the importance of Cx-dependent astrocyte networks in memory processes.